Elevated factor VIII in hereditary haemorrhagic telangiectasia (HHT): Association with venous thromboembolism - Shovlin, Claire L.; Sulaiman, Laila N.; Govani, Fatima S.; Jackson, James E.; Begbie, Megan E. (Thrombosis and Haemostasis, 2007)
Hereditary haemorrhagic telangiectasia (HHT) causes chronic nasal and gastrointestinal haemorrhage. Prothrombotic agents are commonly used for severe haemorrhage. Thrombotic risks have not been defined. In order to identify prothrombotic variables in HHT patients, and assess their potential functional significance, a pilot ELISA-based study comparing plasma proteins in healthy individuals with HHT to age/sex-matched non-HHT controls was validated in a full study of 309 consecutive HHTaffected individuals. In the pilot study, factor VIII (FVIII) and von Willebrand factor antigen concentrations were elevated in the HHT group compared to non-HHT controls (p<0.0013, Mann- Whitney). Service laboratory measurements confirmed high FVIII:Ag in 125 HHT-affected individuals with no recent illhealth, intervention or venous thromboemboli. FVIII:Ag levels increased with age. Logistic regression also suggested an age-independent association with HHT-associated pulmonary arteriovenous malformations (AVMs). No association was demonstrated between FVIII:Ag and acute phase response, disseminated intravascular coagulation, ABO group, pulmonary artery pressure, or markers of HHT haemorrhage. Elevated FVIII:Ag were associated with shortened activated partial thromboplastin times (APTTs), andVTE:VTE affected 20/309 (6.5%) HHT-affected individuals, at median age 61(36–71) years. Four VTE occurred in factorV Leiden heterozygotes in the months following PAVM-associated brain abscess. The strongest association with VTE was with log-transformed FVIII:Ag measured 10–132 months from VTE (odds ratio 2.41, 95% confidence intervals 1.254, 4.612, p=0.008). Age made no additional contribution to VTE risk once adjusted for FVIII:Ag. In conclusion, HHT-related elevation of FVIII:Ag levels may influence thrombotic risk in HHT. Individualised risk-benefit considerations may be helpful in HHT management.
Keywords: Brain abscess; DIC; pulmonary AVMs; tranexamic acid; VWF